Interactive System for Algorithm and Data Structure Visualization - Perháč, Patrik; Šimoňák, Slavomír (Computer science journal of Moldova, 2022)
This work is dedicated to the design, implementation and evaluation of a new algorithm visualization system. The currently available systems and libraries are briefly compared with each other based on the visualizations and functionalities they provide. Since the analyzed tools didn't meet all of the given requirements, we decided that the development of a new system for algorithm and data structure visualizations would be beneficial for use in teaching the subject Data Structures and Algorithms. The new system was designed to be easily usable, extensible, available and to cover the basic functionalities available in similar systems and other useful features. The proposed system provides three types of visualizations: predefined visualizations, to explain how each data structure and algorithm works; interactive visualizations, to let the user interact with the visualization directly; and interactive exercises, to let the users test their knowledge. These three types of visualizations cover the whole learning process, provide theoretical and practical knowledge, and also a way to test their knowledge. The system is implemented in the form of a web application and, for the visualizations, the JSAV library is used. The system was also evaluated by the users via a survey and several improvements were implemented in the system based on the feedback provided by the users.